Atributos químicos do solo, produtividade da soja e do cártamo cultivados sob doses de calcário - Sampaio , Marinez Carpiski (2020)
Most Brazilian soils are naturally acid, and this acidity is responsible for chemical deterioration of the soil, due to the scarcity of basic cations and the toxic effect of aluminum(Al) on plants hindering root development and consequently causing toxic symptoms in the aerial part of crops negatively affecting productivity. This study evaluates the efficiency of surface application of calcite doses on chemical properties of soil in depth and its influence on the development of agronomic characteristics of the soybean and safflower crops during two years of agricultural cultivation. The study happened in an Eutroferric red latossol using a trial design in randomized blocks with eight replicates of 30 m² in a total area of 960 m². The treatments were doses of calcite (48% CaO and 3% MgO), with 75% PRNT, these being: 0, 3, 6 and 9 ton. ha-1, distributed without mechanical incorporation. The soil chemical attributes were evaluated at 12 and 24 months after the experiment at depths of 0-5, 5-10 and 10-20 cm, and the chemical attributes were: pH, H+Al, Al, Ca2+, Mg2+, V% and m%. After applying treatments there were two years of soybean and safflower crops, which development of agronomic and nutritional contents of Ca, Mg and K in soybean leaves were assessed. When it comes to chemical attributes, significant effects of doses on the pH were found at all studied depths, as well as for Al, H+Al, Ca2+, V% and m% at depths of 0-5 and 5-10 cm with 1 year (12 months) and 2 years (24 months) after application of treatments. For the soybean crop, the doses of calcite did not interfere in the development of the agronomic characteristics of the crop, except for the height of plants in the second year of cultivation, when the maximum plant heights were observed using the 3.9 t ha-1 dose. There was an increase in Ca contents in the foliar tissue and a reduction in K contents. There was no interference of calcite doses in the development of safflower crop, providing increase only in the accumulation of dry mass of plants stem in the use of the dose of 6.5 t ha-1. The results demonstrate the efficiency of the use of calcite in the improvement of the Ca contents, neutralization of the toxic effect of Al and the elevation of the pH, increasing the availability of nutrients, raising soil fertility.